Tom and Jerry movie : the fast and the furry [videorecording (DVD)] - Kopp, Bill; Wang, Nathan; Barbera, Joseph; Hanna, William, 1910-2001
Tom and Jerry enter an extreme car race competition called the "Super Race" in order to win the grand prize of a beautiful, new dream mansion. Driving suped-up hot rods that can adapt to any environment (land, sea or air), they compete in this wild race around the world, encountering famous landmarks along the way and leaving chaos in their wake.